The relationship of entrepreneurial values, firm financing and the management and growth performance of small-medium enterprises in Cambodia - Mohd Shariff, Mohd Noor; Peou, Chea (LLC “СPС “Business Perspectives”, 2008)
This study was conducted to examine the relationship between entrepreneurial values, firm financing and management and the growth performance of small-medium enterprises (SMEs) in Cambodia using 220 usable questionnaires that were collected from owners/managers of the firms. The outcomes of hierarchical multiple regression analysis showed that the inclusion of market environment and government policy in the analysis had increased the effect of the relationship between the values of entrepreneurs, firm financing and management and the growth performance of SMEs in Cambodia.Additionally, we also discuss the implications of this study to SME growth performance theory and practice, conceptual and methodological limitations, and directions for future research.